The impact of freshman learning communities on students’ academic performance - Elobaid, Manal; Zidani, Mounia; Koffa, Nesreen; Qadi, Saba (Frontiers in Education, 2024)
IntroductionThe global issue of first-year student retention is a significant concern, generally associated with poor academic performance resulting from insufficient social and intellectual integration. Freshman Learning Communities (FLC) have arisen as a promising approach to tackle these difficulties. This study aims to assess the influence of FLC on the scholastic achievement of first-year undergraduate students.MethodsThe study utilizes quantitative research to determine if involvement in FLC has a favorable impact on academic performance by comparing the performance of students participating in FLC to those who are not part of the program. Descriptive and inferential statistical analyses, including t-tests and ANCOVA, were employed to identify significant differences between the two groups.ResultsSignificant differences were identified, with findings indicating that students participating in the FLC exhibit superior academic performance, reflected in higher grade point averages (GPA). No significant difference was observed in registered and earned credit hours between FLC participants and non-participants.DiscussionThe results suggest that FLC participation is associated with improved academic performance, supporting FLC as a potential strategy to enhance scholastic achievement among first-year students.